Potential Application of Yoga & Ayurveda for Preventing Psychological Burden of Skin Diseases w.s.r. Psoriasis. - Joshi, Priyanka; Singh, O P (International Research Journal of Ayurveda & Yoga, 2023)
Yoga is a traditional art and subtle science of body, mind and soul. Yoga deals with psychosomatic as well as soma-psychotic aspect of the disease, which connects body and mind. The psychosomatic aspect of treatment helps to know the relationship between body and mind. In considering the skin health and disease condition, the first point is to realize that the skin is a different body organ. Covering entire body which helps internal body organ from extreme temperature, attack of the pathogens, and other infections. An organ is defined as a group of cells bundled together in order to fulfil a specific physiological function. Secondly, the health of the skin cannot be neglect from the rest of the body organs. There are many reasons of skin problems but mostly it occurs due to undisciplined lifestyle, lack of sleep, unhealthy food habits, medication, environment and some extent due to genetic factors in some cases. Study have shown, Yoga helps to reduce psychosocial stress and allostatic load through the regular practice of Asana, Pranayama, Shatkarmas and Mudras, these techniques of Yoga work as a panacea in many chronic skin diseases like Psoriasis and related co-morbid conditions like stress, anxiety, depression and improve the quality of life of psoriatic patient.